Preparation method of double-airbag enteroscope outer sleeve
Through the combination of polyvinyl chloride resin with specific materials and ball milling treatment, combined with ultraviolet curing technology, the lack of performance of pure polyvinyl chloride in the medical device field was solved, and excellent impact resistance, high tensile strength, and surface friction coefficient were prepared. Low and antibacterial double airbag small intestinoscope cannula, suitable for medical devices.
Patent Information
- Application Number
- CN202411309580.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The application of pure polyvinyl chloride in the medical device field is limited by its performance such as poor toughness, large surface friction, low tensile strength and no antibacterial properties, making it difficult to meet the needs of double airbag small intestinoscope cannula.
By combining polyvinyl chloride resin with specific stabilizers, chlorinated polyethylene and nano calcium carbonate and other materials, combined with ultraviolet curing technology, we have excellent impact resistance, high tensile strength and low surface friction coefficient to prepare a high surface resistance. And antibacterial double airbag small intestinoscope cannula.
It realizes the high toughness, low friction and antibacteriality of the double airbag small intestine cannula. It is suitable for use in the medical device field, especially for the double airbag small intestine cannula, ensuring the safety and comfort of the equipment.
Smart Images

Figure BDA0005050260040000151 
Figure BDA0005050260040000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical devices, and in particular relates to a method for preparing a double-balloon enteroscope outer sleeve. Background Art
[0002] Double-balloon enteroscope is an advanced medical examination device, which consists of an endoscope and an outer sleeve, each with a balloon at the distal end. This design allows the small intestine to be opened by alternating inflation of the two balloons, thereby achieving a comprehensive examination of the small intestine. As an important component, the outer sleeve not only needs to have sufficient strength and toughness to support the operation of the endoscope, but also needs to ensure comfort and safety during the examination.
[0003] As an important thermoplastic, polyvinyl chloride (PVC) has been widely used in many fields such as construction, electricity, home appliances, packaging, and automobiles due to its excellent chemical corrosion resistance, wear resistance, electrical insulation, and good processing performance. However, pure PVC still has some shortcomings in performance, such as poor toughness, high surface friction, low tensile strength, and no antibacterial properties, which limits its application in the field of medical devices.
[0004] Therefore, if PVC is to be used in the preparation of double-balloon enteroscope outer sleeve, it needs to be modified, toughened and strengthened to improve its comprehensive performance. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a double-balloon enteroscope outer sleeve, which not only has excellent impact resistance but also has high tensile strength, non-toxic and harmless raw materials, low surface friction coefficient and good antibacterial property.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a double-balloon enteroscope outer sleeve comprises the following steps:
[0008] S1, mixing a polyvinyl chloride resin and a first stabilizer, ball milling for 1 to 3 hours, adding chlorinated polyethylene, and continuing ball milling for 0.5 to 1 hour to obtain a modified polyvinyl chloride resin;
[0009] S2. After mixing the second stabilizer, modified polyvinyl chloride resin, crosslinking agent and dispersant, add processing aid, mix well, add lubricant and reinforcing agent, mix well, mix at 170-190° C. for 5-10 min, keep warm and press at 180-200° C. and 10-20 MPa for 4-8 min, transfer to cold press for 10-15 min, and press out initial samples with dimensions in accordance with GB11751-1989 "Medical Polymer Hose Size Series";
[0010] S3. Soak the initial sample in the pretreatment solution for 1 to 2 hours, wash it with deionized water and dry it, soak it in the precursor solution for 1 to 2 minutes, take it out, and UV-cure it for 20 to 30 minutes to obtain the double-balloon enteroscope outer sleeve.
[0011] Preferably, the polyvinyl chloride resin includes a first polyvinyl chloride resin and a second polyvinyl chloride resin.
[0012] Preferably, the mass ratio of the first polyvinyl chloride resin to the second polyvinyl chloride resin is (2-4):1; more preferably, it is 3:1.
[0013] Preferably, the K value of the first polyvinyl chloride resin is 66-68, the average degree of polymerization is 1000-1100, and the viscosity is 107-118 mL / g.
[0014] Preferably, the second polyvinyl chloride resin has a K value of 55 to 59, an average degree of polymerization of 650 to 750, and a viscosity of 73 to 86 mL / g.
[0015] In some preferred embodiments, the first polyvinyl chloride resin and the second polyvinyl chloride resin are both purchased from Jining Beinuoke Biotechnology Co., Ltd., SG-5 and SG-8.
[0016] Preferably, the first stabilizer and the second stabilizer are both a mixture of zinc stearate and calcium stearate.
[0017] Preferably, the mass ratio of zinc stearate to calcium stearate is (1-3):1; more preferably, it is 2:1.
[0018] In some preferred solutions, calcium stearate and zinc stearate are selected as stabilizers, and the two can synergize the stability of PVC composite particles. This is because zinc stearate can replace active chlorine and absorb HCl, while calcium stearate can capture HCl and replace chloride generated by zinc stearate to regenerate it. This synergistic effect can significantly improve the stability of PVC. Moreover, both stabilizers are non-toxic, so that the prepared PVC composite particles can be used in the field of medical devices.
[0019] Preferably, the added amount of the first stabilizer is 0.5% to 2% of the polyvinyl chloride resin.
[0020] Preferably, the chlorinated polyethylene includes a first chlorinated polyethylene and a second chlorinated polyethylene.
[0021] Preferably, the mass ratio of the first chlorinated polyethylene to the second chlorinated polyethylene is 1:(0.5-2); further preferably, it is 1:1.
[0022] Preferably, the added amount of the chlorinated polyethylene is 50% to 60% of the mass of the polyvinyl chloride resin.
[0023] Preferably, the first chlorinated polyethylene has a tensile strength of 8 to 13 MPa, a chlorine content of 33% to 37%, and a hardness of ≤65A.
[0024] In some preferred embodiments, the first chlorinated polyethylene is purchased from Shandong Bangtai Petrochemical.
[0025] Preferably, the second chlorinated polyethylene has a chlorine content of ≥67%, a thermal decomposition temperature of 110° C., and a viscosity of 10 to 20S.
[0026] In some preferred embodiments, the second chlorinated polyethylene is purchased from Shandong Ketian Chemical Co., Ltd.
[0027] The inventors found that the toughness of the double-balloon enteroscope outer tube can be improved by compounding two specific polyvinyl chloride resins. This may be because the synergistic effect of the two different polyvinyl chlorides can not only achieve complementary mechanical properties, but also form a stronger structural network through interfacial interaction, thereby further improving toughness. In addition, by adding two specific chlorinated polyethylenes, the compatibility of chlorinated polyethylene and polyvinyl chloride resin can be improved while toughening, but the blending treatment has limited effect on improving the compatibility of chlorinated polyethylene and polyvinyl chloride resin, which in turn affects the toughening effect.
[0028] The inventors have found through a large number of experiments that before blending with other raw materials, the polyvinyl chloride resin is first ball-milled and then ball-milled with chlorinated polyethylene, which can greatly improve the compatibility of chlorinated polyethylene and polyvinyl chloride resin, thereby improving its tensile strength and toughness. This may be because ball milling can not only destroy polyvinyl chloride resin particles to cause chain scission and degradation, but also produce a certain number of active sites. After the introduction of chlorinated polyethylene, the instantaneous high temperature caused by ball milling can enable chlorinated polyethylene to be coated on the surface of polyvinyl chloride resin, and a grafting reaction occurs with the active sites produced by polyvinyl chloride resin, which greatly improves the interaction between the two phases in the two materials, thereby achieving interface strengthening, forming a stable network structure, and improving the toughness and tensile strength of the double-balloon enteroscope outer sleeve. However, too long ball milling time will cause excessive plasticization of polyvinyl chloride resin, affecting the impact resistance of the product, and only chlorinated polyethylene has limited improvement in product performance.
[0029] The initial sample is prepared from the following raw materials, calculated by weight: 100-120 parts of modified polyvinyl chloride resin, 0.5-2 parts of cross-linking agent, 0.1-2 parts of dispersant, 2-4 parts of processing aid, 15-30 parts of reinforcing agent, 0.5-3 parts of second stabilizer, and 1-5 parts of lubricant.
[0030] Preferably, the cross-linking agent is dicumyl peroxide.
[0031] Preferably, the dispersing agent is polyvinyl alcohol and hydroxypropyl methylcellulose.
[0032] Preferably, the mass ratio of the polyvinyl alcohol to hydroxypropyl methylcellulose is 1:(0.5-2); further preferably, it is 1:1.
[0033] Preferably, the alcoholysis degree of the polyvinyl alcohol is ≥99%, the ash content is ≤0.5%, and the viscosity of the polyvinyl alcohol prepared into a 4 wt % aqueous solution is 15-25 CP.
[0034] In some preferred embodiments, the polyvinyl alcohol is purchased from Japan Kuraray polyvinyl alcohol 80-18.
[0035] Preferably, the hydroxypropyl methylcellulose has a methoxy content of 28% to 30%, a hydroxypropyl content of 7% to 12%, and a gel temperature of 58 to 64°C.
[0036] In some preferred embodiments, the hydroxypropyl methylcellulose is purchased from Shandong Weifang LiTe Composite Materials Co., Ltd.
[0037] Preferably, the processing aid is an acrylic copolymer.
[0038] Preferably, the glass transition temperature of the acrylic copolymer is -55 to -45°C, the average torque is 22 to 28 Nm, and the Shore hardness is 80 to 85A; further preferably, the glass transition temperature of the acrylic copolymer is -52 to -48°C, the average torque is 25.7 Nm, and the Shore hardness is 82.1A.
[0039] In some preferred embodiments, the processing aid is purchased from Shandong Hongfu Chemical Co., Ltd.
[0040] Preferably, the reinforcing agent is modified nano calcium carbonate.
[0041] The preparation method of the modified nano calcium carbonate comprises the following steps: mixing the nano calcium carbonate and a polymer modifier at a high speed for 5 to 10 minutes to obtain the modified nano calcium carbonate.
[0042] Preferably, the nano-calcium carbonate includes a first nano-calcium carbonate, a second nano-calcium carbonate, and a third nano-calcium carbonate.
[0043] Preferably, the mass ratio of the first nano-calcium carbonate, the second nano-calcium carbonate, and the third nano-calcium carbonate is 1:(0.5-2):(0.5-2); further preferably, it is 1:1:1.
[0044] Preferably, the average particle size of the first nano-calcium carbonate is 10 nm.
[0045] Preferably, the average particle size of the second nano-calcium carbonate is 50 nm.
[0046] Preferably, the average particle size of the third nano-calcium carbonate is 100 nm.
[0047] In some preferred embodiments, the first nano-calcium carbonate, the second nano-calcium carbonate, and the third nano-calcium carbonate are all purchased from Zhongke Yannuo (Beijing) Technology Co., Ltd.
[0048] The inventors found that the use of three different nano-calcium carbonates as reinforcing agents can improve the strength and toughness of polyvinyl chloride composite particles. This may be because, on the one hand, the three different nano-calcium carbonates can form a particle size complementary effect in the PVC matrix. Larger nanoparticles can act as stress concentration points to cause silver streaks or cavitation effects, while smaller nanoparticles can fill these defects and stop the expansion of cracks. This particle size complementary effect helps to form a denser toughening network and improve the overall performance of the composite material. On the other hand, the interface bonding between nano-calcium carbonate of different particle sizes and the PVC matrix may also produce a synergistic effect. Larger nanoparticles may have a larger specific surface area and more surface functional groups, thereby forming a stronger interface bond with the matrix. Smaller nanoparticles may more easily penetrate into the matrix and fill micropores and defective areas, further improving the interface bonding strength, and then improving the mechanical properties of the composite particles such as impact resistance. However, its improvement effect is limited, and the dispersibility of nano-calcium carbonate in the PVC system is poor.
[0049] Preferably, the polymer modifier is liquid nitrile rubber and hydroxyl-terminated polybutadiene.
[0050] Preferably, the viscosity of the liquid nitrile rubber at 25° C. is 300 Pa·s, and the acrylonitrile content is 30% to 33%.
[0051] In some preferred embodiments, the liquid nitrile rubber is purchased from Shandong Wang's Brothers Rubber & Plastic Technology Co., Ltd., LNBR815E.
[0052] Preferably, the hydroxyl value of the hydroxy-terminated polybutadiene is 0.54-0.64 mmol / g, the viscosity at 40° C. is ≤8.5 Pa·s, and the number average molecular weight is 3.3-4.1×10 3 .
[0053] In some preferred embodiments, the hydroxy-terminated polybutadiene is purchased from Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd.
[0054] Preferably, the mass ratio of the liquid nitrile rubber to the hydroxy-terminated polybutadiene is 1:(0.5-2); further preferably, it is 1:1.
[0055] Preferably, the added amount of the polymer modifier is 5% to 15% of the nano-calcium carbonate.
[0056] The inventor found that by selecting two different polymer modifiers to modify three kinds of nano calcium carbonate at the same time, the stability of nano calcium carbonate in the system can be improved, thereby further improving the toughness and tensile strength of the double balloon enteroscope outer tube prepared. This may be because on the one hand, two polymer modifiers containing specific groups can be coated with the surface of calcium carbonate to form a core-shell structure, and it is applied to this system, which can not only improve the plasticizing effect on PVC, but also form a three-dimensional network structure in the PVC matrix, thereby improving the resistance and heat resistance of the composite particles, and can make the nano calcium carbonate of different particle sizes achieve good dispersion in the PVC matrix, thereby helping to reduce the agglomeration phenomenon of nano particles and improve its toughening and strengthening effect, and on the other hand, the two polymer modifiers also have a certain toughening effect on PVC, which can improve the impact resistance of the composite particles while not affecting its tensile strength, and have a synergistic toughening effect with nano calcium carbonate. However, there will still be more agglomerated particles in the system with too high an amount of nano calcium carbonate added, and cracks and stress cracking are prone to occur under the action of external forces, affecting the tensile properties and impact resistance of the composite particles. Although excessive addition of polymer modifiers can significantly improve impact resistance, its tensile strength will decrease.
[0057] Preferably, the lubricant is one or more of paraffin wax, polyethylene wax, carbon black, stearic acid monoglyceride, and oleic acid ester, and more preferably, it is paraffin wax, polyethylene wax, and carbon black.
[0058] Preferably, the mass ratio of the paraffin wax, polyethylene wax and carbon black is (3-5):1:(1-3); further preferably, it is 4:1:2.
[0059] Preferably, the melting point of the paraffin wax is 58-60° C., the needle penetration is 17 mm, and the oil content is ≤0.8%.
[0060] In some preferred embodiments, the paraffin wax is purchased from Hubei Xingdongcheng Chemical Co., Ltd.
[0061] Preferably, the polyethylene wax has a softening point of 90 to 100° C., a viscosity of 10 to 20 cps at 140° C., and a molecular weight of 1000 to 2000 mg KOH / g.
[0062] In some preferred embodiments, the polyethylene wax is purchased from Changzhou Kesa Chenggong Plastic Materials.
[0063] Preferably, the carbon black has a particle size of 20 nm, a nitrogen attachment specific surface area of 140 m2 / g, and a volatilization amount of 1%.
[0064] In some preferred embodiments, the carbon black is purchased from Mitsubishi of Japan, MA600.
[0065] Preferably, the pretreatment solution is a benzophenone-acetone solution with a benzophenone mass fraction of 10% to 15%.
[0066] The inventors found that the bonding strength between the coating and the primary sample can be greatly improved by pre-treating with a pre-treatment solution before immersing in the precursor solution. This may be because benzophenone will separate a hydrogen atom from the polyvinyl chloride network under the action of ultraviolet light and generate a free radical, thereby providing an active site on the surface of the primary sample prepared from polyvinyl chloride, so that the coating network is not only connected to the polymer chain in the coating, but also successfully grafted with the polyvinyl chloride polymer network, making the coating more reliable, so that the prepared double-balloon enteroscope outer sleeve has excellent toughness, as well as excellent anti-friction and antibacterial properties, and will not cause tissue contusion in the human body in practical applications, and can also reduce the probability of infection.
[0067] The preparation method of the precursor solution comprises the following steps: dissolving acrylamide, polyvinyl pyrrolidone and quaternary ammonium salt chitosan in deionized water, stirring and dissolving, adding zinc dimethacrylate solution, continuing to stir until completely dissolved, and defoaming to obtain the precursor solution.
[0068] Preferably, the mass ratio of acrylamide, polyvinyl pyrrolidone and quaternary ammonium salt chitosan is (2-4):1:(0.1-0.5); further preferably, it is 10:3:1.
[0069] Preferably, the solid-to-liquid ratio of the total mass of acrylamide, polyvinyl pyrrolidone, quaternary ammonium salt chitosan and deionized water is 1 g: (1.5-3) mL; more preferably, it is 1 g: 2 mL.
[0070] Preferably, the zinc dimethacrylate solution is a zinc dimethacrylate-N,N-dimethylformamide solution in which the mass fraction of zinc dimethacrylate is 50% to 55%.
[0071] Preferably, the volume ratio of the zinc dimethacrylate solution to deionized water is 1:(3-5); further preferably, it is 1:4.
[0072] Considering that the enteroscope outer tube will directly contact the intestine, the pipeline not only needs to have excellent toughness and tensile strength, but also the outer wall of the pipeline must be smooth and have certain antibacterial properties. The inventor found that soaking the prepared initial sample in a specific precursor solution can make the surface of the prepared double-balloon enteroscope outer tube smooth and have certain antibacterial properties. This may be because acrylamide, zinc dimethacrylate and polyvinyl pyrrolidone can work together to form a polymer coating, while also improving the hydrophilicity and biocompatibility of the coating and reducing the friction coefficient of the coating. On the other hand, the zinc ions in zinc dimethacrylate can synergize with quaternary ammonium salt chitosan to form a complex, thereby forming a semi-interpenetrating network, so that the connection between the polymer chains is closer, while improving the tensile properties of the coating, it can also adsorb the negative charge on the surface of the bacteria, resulting in bacterial membrane rupture and bacterial death, and improving the antibacterial and antifouling effect of the coating. However, the prepared coating and the initial sample prepared based on polyvinyl chloride resin have weak binding ability, and the coating is easy to fall off, affecting product performance.
[0073] The second aspect of the present invention provides a double-balloon enteroscope outer sleeve prepared by the preparation method of the double-balloon enteroscope outer sleeve.
[0074] The third aspect of the present invention provides application of the double-balloon enteroscope outer sleeve in the medical field.
[0075] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0076] 1. The present invention provides a double-balloon enteroscope outer sleeve, which not only has excellent impact resistance, but also has high tensile strength. The raw materials are non-toxic and harmless, and the surface friction coefficient is low and the antibacterial property is good. It is very suitable for application in the field of medical devices, especially for double-balloon enteroscope outer sleeve.
[0077] 2. The present invention selects two specific polyvinyl chloride resins for compounding, which can improve the toughness of the double-balloon enteroscope outer sleeve.
[0078] 3. The present invention firstly ball-mills the polyvinyl chloride resin before blending with other raw materials, and then ball-mills it with chlorinated polyethylene, which can greatly improve the compatibility of chlorinated polyethylene and polyvinyl chloride resin, thereby improving its tensile strength and toughness.
[0079] 4. The present invention can improve the strength and toughness of polyvinyl chloride composite particles by selecting three nano calcium carbonates with different particle sizes as reinforcing agents.
[0080] 5. The present invention uses two different polymer modifiers to modify three types of nano-calcium carbonate at the same time, which can improve the stability of the nano-calcium carbonate in the system, thereby further improving the toughness and tensile strength of the prepared double-balloon enteroscope outer sleeve.
[0081] 6. The present invention soaks the prepared initial sample in a specific precursor solution, so that the surface of the prepared double-balloon enteroscope outer sleeve is smooth and has certain antibacterial properties.
[0082] 7. The present invention uses a pretreatment solution for pretreatment before immersing in the precursor solution, which can greatly improve the bonding force between the coating and the initial sample. DETAILED DESCRIPTION
[0083] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0084] The raw materials used in the present invention are all commercially available, specifically:
[0085] The K value of the first polyvinyl chloride resin is 66-68, the average degree of polymerization is 1000-1100, and the viscosity is 107-118 mL / g; the K value of the second polyvinyl chloride resin is 55-59, the average degree of polymerization is 650-750, and the viscosity is 73-86 mL / g; both are purchased from Jining Benoke Biotechnology Co., Ltd., SG-5 and SG-8.
[0086] The first chlorinated polyethylene has a tensile strength of 8-13 MPa, a chlorine content of 33%-37%, a hardness of ≤65A, and is purchased from Shandong Bangtai Petrochemical.
[0087] The second chlorinated polyethylene has a chlorine content of ≥67%, a thermal decomposition temperature of 110° C., and a viscosity of 10-20S, and is purchased from Shandong Ketian Chemical Co., Ltd.
[0088] The alcoholysis degree of polyvinyl alcohol is ≥99%, the ash content is ≤0.5%, and the viscosity of the polyvinyl alcohol prepared into a 4wt% aqueous solution is 15-25CP; polyvinyl alcohol 80-18 purchased from Kuraray of Japan.
[0089] The methoxy content of hydroxypropyl methylcellulose is 28% to 30%, the hydroxypropyl content is 7% to 12%, and the gel temperature is 58 to 64° C.; it was purchased from Shandong Weifang Li Te Composite Materials Co., Ltd.
[0090] The acrylic copolymer has a glass transition temperature of -52 to -48°C, an average torque of 25.7 Nm, and a Shore hardness of 82.1A, and is purchased from Shandong Hongfu Chemical Co., Ltd.
[0091] The average particle size of the first nano-calcium carbonate is 10 nm; the average particle size of the second nano-calcium carbonate is 50 nm; the average particle size of the third nano-calcium carbonate is 100 nm; all are purchased from Zhongke Yannuo (Beijing) Technology Co., Ltd.
[0092] The liquid nitrile rubber has a viscosity of 300 Pa·s at 25° C. and an acrylonitrile content of 30% to 33%; it was purchased from Shandong Wangshi Brothers Rubber & Plastic Technology, LNBR 815E.
[0093] The hydroxyl value of hydroxy-terminated polybutadiene is 0.54-0.64 mmol / g, the viscosity at 40°C is ≤8.5 Pa·s, and the number average molecular weight is 3.3-4.1×10 3 ; Purchased from Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd.
[0094] The melting point of paraffin wax is 58-60°C, the needle penetration is 17mm, and the oil content is ≤0.8%; it was purchased from Hubei Xingdongcheng Chemical Co., Ltd.
[0095] The polyethylene wax has a softening point of 90-100° C., a viscosity of 10-20 cps at 140° C., and a molecular weight of 1000-2000 mg KOH / g; it was purchased from Changzhou Kesai Chenggong Plastic Materials.
[0096] The particle size of carbon black is 20nm, and the nitrogen adhesion specific surface area is 140m 2 / g, volatile content is 1%; purchased from Mitsubishi, Japan, MA600.
[0097] Example 1
[0098] This embodiment provides a method for preparing a double-balloon enteroscope outer sleeve, comprising the following steps:
[0099] S1, mixing a polyvinyl chloride resin and a first stabilizer, ball milling for 2 hours, adding chlorinated polyethylene, and continuing ball milling for 0.5 hours to obtain a modified polyvinyl chloride resin;
[0100] S2. After mixing the second stabilizer, modified polyvinyl chloride resin, crosslinking agent and dispersant, add processing aid, mix well, add lubricant and reinforcing agent, mix well, mix at 180°C for 8 minutes, keep warm and press at 190°C and 15MPa for 6 minutes, transfer to a cold press for 12 minutes, and press out a preliminary sample with a size that meets GB 11751-1989 "Medical Polymer Hose Size Series";
[0101] S3. Soak the initial sample in the pretreatment solution for 1.5 hours, wash with deionized water and dry, soak it in the precursor solution for 2 minutes, take it out, and UV-cure it for 25 minutes to obtain a double-balloon enteroscope outer sleeve.
[0102] The polyvinyl chloride resin is a first polyvinyl chloride resin and a second polyvinyl chloride resin.
[0103] The mass ratio of the first polyvinyl chloride resin to the second polyvinyl chloride resin is 3:1.
[0104] The first stabilizer and the second stabilizer are both a mixture of zinc stearate and calcium stearate.
[0105] The mass ratio of the zinc stearate to the calcium stearate is 2:1.
[0106] The added amount of the first stabilizer is 1% of the polyvinyl chloride resin.
[0107] The chlorinated polyethylenes are first chlorinated polyethylenes and second chlorinated polyethylenes.
[0108] The mass ratio of the first chlorinated polyethylene to the second chlorinated polyethylene is 1:1.
[0109] The added amount of the chlorinated polyethylene is 55% of the mass of the polyvinyl chloride resin.
[0110] The initial sample is prepared from the following raw materials, calculated by weight: 110 parts of polyvinyl chloride resin, 1 part of cross-linking agent, 1 part of dispersant, 3 parts of processing aid, 25 parts of reinforcing agent, 2 parts of second stabilizer, and 3 parts of lubricant.
[0111] The cross-linking agent is dicumyl peroxide.
[0112] The dispersants are polyvinyl alcohol and hydroxypropyl methylcellulose.
[0113] The mass ratio of the polyvinyl alcohol to the hydroxypropyl methylcellulose is 1:1.
[0114] The processing aid is an acrylic acid ester copolymer.
[0115] The reinforcing agent is modified nano calcium carbonate.
[0116] The preparation method of the modified nano calcium carbonate comprises the following steps: mixing the nano calcium carbonate and the polymer modifier at high speed for 8 minutes to obtain the modified nano calcium carbonate.
[0117] The nano calcium carbonate includes a first nano calcium carbonate, a second nano calcium carbonate and a third nano calcium carbonate.
[0118] The mass ratio of the first nano-calcium carbonate, the second nano-calcium carbonate, and the third nano-calcium carbonate is 1:1:1.
[0119] The polymer modifiers are liquid nitrile rubber and hydroxyl-terminated polybutadiene.
[0120] The mass ratio of the liquid nitrile rubber to the hydroxy-terminated polybutadiene is 1:1.
[0121] The addition amount of the polymer modifier is 10% of the nano calcium carbonate.
[0122] The lubricants are paraffin wax, polyethylene wax and carbon black.
[0123] The mass ratio of the paraffin wax, polyethylene wax and carbon black is 4:1:2.
[0124] The pretreatment solution is a benzophenone-acetone solution with a benzophenone mass fraction of 12%.
[0125] The preparation method of the precursor solution comprises the following steps: dissolving acrylamide, polyvinyl pyrrolidone and quaternary ammonium salt chitosan in deionized water, stirring and dissolving, adding zinc dimethacrylate solution, continuing to stir until completely dissolved, and defoaming to obtain the precursor solution.
[0126] The mass ratio of acrylamide, polyvinyl pyrrolidone and quaternary ammonium salt chitosan is 10:3:1.
[0127] The solid-to-liquid ratio of the total mass of the acrylamide, polyvinyl pyrrolidone, quaternary ammonium salt chitosan and deionized water is 1 g:2 mL.
[0128] The zinc dimethacrylate solution is a zinc dimethacrylate-N,N-dimethylformamide solution with a zinc dimethacrylate mass fraction of 50%.
[0129] The volume ratio of the zinc dimethacrylate solution to deionized water is 1:4.
[0130] Example 2
[0131] The difference between this embodiment and embodiment 1 is that the mass ratio of the first polyvinyl chloride resin to the second polyvinyl chloride resin is 4:1.
[0132] Example 3
[0133] The difference between this embodiment and embodiment 1 is that the mass ratio of the liquid nitrile rubber to the hydroxyl-terminated polybutadiene is 1:2.
[0134] Comparative Example 1
[0135] The difference between this comparative example and Example 1 is that the polyvinyl chloride resin is the first polyvinyl chloride resin.
[0136] Comparative Example 2
[0137] The difference between this comparative example and Example 1 is that the chlorinated polyethylene is the first chlorinated polyethylene.
[0138] Comparative Example 3
[0139] The difference between this comparative example and Example 1 is as follows: S1, a polyvinyl chloride resin is mixed with a first stabilizer, and after ball milling for 4 hours, chlorinated polyethylene is added, and the ball milling is continued for 0.5 hours to obtain a modified polyvinyl chloride resin.
[0140] Comparative Example 4
[0141] The difference between this comparative example and Example 1 is as follows: after the stabilizer, polyvinyl chloride resin, chlorinated polyethylene, crosslinking agent and dispersant are mixed, a processing aid is added, and after mixing evenly, a lubricant and a reinforcing agent are added, and after mixing evenly, the mixture is kneaded at 180° C. for 8 minutes, and then kept at 190° C. and 15 MPa for 6 minutes, and then transferred to a cold press for cold pressing for 12 minutes to press out a preliminary sample whose size meets the requirements of GB11751-1989 "Medical Polymer Hose Size Series".
[0142] The raw materials for preparing the initial sample are, by weight: 110 parts of polyvinyl chloride resin, 55 parts of polyvinyl chloride resin, 1 part of cross-linking agent, 1 part of dispersant, 3 parts of processing aid, 25 parts of reinforcing agent, 4 parts of stabilizer, and 3 parts of lubricant.
[0143] Comparative Example 5
[0144] The difference between this comparative example and Example 1 is that the mass ratio of the first nano-calcium carbonate, the second nano-calcium carbonate and the third nano-calcium carbonate is 1:3:3.
[0145] Comparative Example 6
[0146] The difference between this comparative example and Example 1 is that the initial sample is prepared from the following raw materials, by weight: 110 parts of polyvinyl chloride resin, 1 part of cross-linking agent, 1 part of dispersant, 3 parts of processing aid, 40 parts of reinforcing agent, 2 parts of second stabilizer, and 3 parts of lubricant.
[0147] Comparative Example 7
[0148] The difference between this comparative example and Example 1 is that the addition amount of the polymer modifier is 20% of the nano calcium carbonate.
[0149] Comparative Example 8
[0150] The difference between this comparative example and Example 1 is as follows: S3, the initial sample is soaked in the precursor solution for 2 minutes, then taken out, and UV-cured for 25 minutes to obtain a double-balloon enteroscope outer sleeve.
[0151] Comparative Example 9
[0152] The difference between this comparative example and Example 1 is that the preparation method of the precursor solution comprises the steps of dissolving acrylamide, polyvinyl pyrrolidone and quaternary ammonium salt chitosan in deionized water, stirring and dissolving, and then defoaming to obtain the precursor solution.
[0153] Performance Testing
[0154] The impact resistance of the small enteroscope outer sleeve was tested with reference to GB / T16420-1996; the tensile strength of the small enteroscope outer sleeve was tested with reference to GB / T1043-1992; the friction coefficient of the small enteroscope outer sleeve was tested with reference to GB / T 10006-2021; Escherichia coli was used as a representative, and the antibacterial property of the small enteroscope outer sleeve was tested with reference to GB / T39101-2020, and the diameter of the inhibition zone was recorded. The results are shown in Table 1.
[0155] Table 1 Measurement results
[0156]
[0157]
[0158] According to statistics, the double-balloon enteroscope outer sleeves prepared in Examples 1 to 3 of the present invention have high impact resistance and tensile strength, low friction coefficient, and large antibacterial zone diameter, indicating that the surface is smooth and has a certain antibacterial effect. In Comparative Example 1, no second polyvinyl chloride resin was added, in Comparative Example 2, no second chlorinated polyethylene was added, in Comparative Example 3, the ball milling time was too long, in Comparative Example 4, no ball milling treatment was performed, in Comparative Example 5, too much second nano-calcium carbonate and third nano-calcium carbonate were added, in Comparative Example 6, the overall amount of nano-calcium carbonate added was too high, in Comparative Example 7, the amount of polymer modifier added was too high, in Comparative Example 8, no pretreatment solution was used for pretreatment, in Comparative Example 9, zinc dimethylacrylate was not added to the precursor solution, and the prepared double-balloon enteroscope outer sleeve had poor impact resistance and tensile properties, a high friction coefficient, and a small antibacterial zone diameter. Therefore, the double-balloon enteroscope outer sleeve prepared using the raw materials and methods described in the present application not only has excellent impact resistance, but also has high tensile strength, the raw materials are non-toxic and harmless, and the surface friction coefficient is low, and the antibacterial property is good, which is very suitable for application in the field of medical devices, especially for double-balloon enteroscope outer sleeves.
[0159] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a double-balloon enteroscope outer sleeve, characterized in that: The following steps are involved: S1, mixing a polyvinyl chloride resin and a first stabilizer, ball milling for 1 to 3 hours, adding chlorinated polyethylene, and continuing ball milling for 0.5 to 1 hour to obtain a modified polyvinyl chloride resin; S2. After mixing the second stabilizer, modified polyvinyl chloride resin, crosslinking agent and dispersant, add processing aid, mix well, add lubricant and reinforcing agent, mix well, mix at 170-190° C. for 5-10 min, then keep warm and press at 180-200° C. and 10-20 MPa for 4-8 min, transfer to a cold press and cold press for 10-15 min, and press out a preliminary sample with a size conforming to GB 11751-1989; S3, soaking the initial sample in the pretreatment solution for 1 to 2 hours, washing with deionized water and drying, soaking it in the precursor solution for 1 to 2 minutes, taking it out, and UV curing it for 20 to 30 minutes to obtain a double-balloon enteroscope outer sleeve; The polyvinyl chloride resin includes a first polyvinyl chloride resin and a second polyvinyl chloride resin; The K value of the first polyvinyl chloride resin is 66-68, the average degree of polymerization is 1000-1100, and the viscosity is 107-118 mL / g; the K value of the second polyvinyl chloride resin is 55-59, the average degree of polymerization is 650-750, and the viscosity is 73-86 mL / g; the chlorinated polyethylene includes a first chlorinated polyethylene and a second chlorinated polyethylene; the first chlorinated polyethylene has a tensile strength of 8-13 MPa, a chlorine content of 33%-37%, and a hardness of ≤65A; the second chlorinated polyethylene has a chlorine content of ≥67%, a thermal decomposition temperature of 110°C, and a viscosity of 10-20S.
2. The method for preparing the double-balloon enteroscope outer sleeve according to claim 1, characterized in that: The initial sample is prepared from the following raw materials, calculated by weight: 100-120 parts of modified polyvinyl chloride resin, 0.5-2 parts of cross-linking agent, 0.1-2 parts of dispersant, 2-4 parts of processing aid, 15-30 parts of reinforcing agent, 0.5-3 parts of second stabilizer, and 1-5 parts of lubricant.
3. The method for preparing the double-balloon enteroscope outer sleeve according to claim 2, characterized in that: The processing aid is an acrylic acid ester copolymer.
4. The method for preparing the double-balloon enteroscope outer sleeve according to claim 3, characterized in that: The acrylic copolymer has a glass transition temperature of -55 to -45°C, an average torque of 22 to 28 Nm, and a Shore hardness of 80 to 85A.
5. The method for preparing the double-balloon enteroscope outer sleeve according to claim 2, characterized in that: The reinforcing agent is modified nano calcium carbonate.
6. The method for preparing the double-balloon enteroscope outer sleeve according to claim 5, characterized in that: The preparation method of the modified nano calcium carbonate comprises the following steps: mixing the nano calcium carbonate and a polymer modifier at a high speed for 5 to 10 minutes to obtain the modified nano calcium carbonate.
7. The method for preparing the double-balloon enteroscope outer sleeve according to claim 6, characterized in that: The polymer modifiers are liquid nitrile rubber and hydroxyl-terminated polybutadiene.
8. The method for preparing the double-balloon enteroscope outer sleeve according to claim 7, characterized in that: The liquid nitrile rubber has a viscosity of 300 Pa·s at 25°C and an acrylonitrile content of 30% to 33%. The hydroxyl value of the hydroxy-terminated polybutadiene is 0.54 to 0.64 mmol / g, a viscosity of ≤8.5 Pa·s at 40°C, and a number average molecular weight of 3.3 to 4.1×10 3 .
9. A double-balloon enteroscope outer sleeve prepared according to the method for preparing a double-balloon enteroscope outer sleeve according to any one of claims 1 to 8.
10. Use of the double-balloon enteroscope outer sleeve according to claim 9 in the field of medical devices.
